2020
DOI: 10.1177/1082013220954606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size on structural, physicochemical, and functional properties of potato residue from starch isolation and quality characteristics of residue-based starch noodles

Abstract: The structural, physicochemical, and functional properties of potato residue with different mesh sizes (<180 µm, <150 µm, <106 µm, <75 µm, ultrafine) obtained from starch isolation were investigated, and its effects on the shear strength, tensile strength, cooking time, and in vitro digestibility of 5% potato residue-based starch noodles were further compared. The results showed that the protein, ash, dietary fiber, water holding capacity, and water solubility of fractionated potato residue were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…SWC and WHC of seaweeds depend largely on the amount of protein and total dietary fibers present in their composition [6]. Also, lesser particle size with more surface area indicates higher WHC [25]. Both SWC and WHC directly affect the texture, mouthfeel, and freshness of the food products.…”
Section: Functional Properties Figurementioning
confidence: 99%
“…SWC and WHC of seaweeds depend largely on the amount of protein and total dietary fibers present in their composition [6]. Also, lesser particle size with more surface area indicates higher WHC [25]. Both SWC and WHC directly affect the texture, mouthfeel, and freshness of the food products.…”
Section: Functional Properties Figurementioning
confidence: 99%
“…Liu et al ( 2021 ) found that low‐amylose rice starch significantly increased the tensile strength and hardness of potato starch noodles, whereas waxy rice starch had the reverse effect. Waliullah et al ( 2021 ) reported that the textural properties of starch noodles could be improved by ultrafine sweet potato residues. Odabas et al ( 2022 ) discovered that the hardness of gluten‐free noodles ranged from 7.1 to 14.0 N, with no apparent relationship to the amount of yellow lentil flour.…”
Section: Resultsmentioning
confidence: 99%
“…Superfine grinding, as a novel technique, is an efficient tool for making superfine powder. The superfine powders (approximately 10–30 μm in size) exhibit excellent characteristics, such as better surface properties, stronger solubility and fluidity, better flavor release, and mouthfeel (Waliullah et al, 2021 ). This technology has been commonly applied in the food industry, and the superfine powders of Sargassum fusiforme residue (SFR), red grape pomace, Vaccinium bracteatum Thunb leaves, and Sanchi ( Panax notoginseng ) flower have been reported (Gan et al, 2022 ; Jiang et al, 2017 ; Wu et al, 2020 ; Zhao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each ultrafine Kudzu powder sample (flowers and roots) was examined in three portions. According to the procedures previously outlined [ 27 ], they were uniformly distributed in the scanning electron microscopy (SEM) sample stage. After the gold spray coating of the particles and setting the accelerating voltage at 3 kV A, at a distance of 12.5 mm, and at 500× and 1000× magnification, photographs of the structure and surface morphology of the Kudzu powders were seen and recorded.…”
Section: Methodsmentioning
confidence: 99%